Examining wage inequality among women in India: A multidimensional analysis of socio-economic disparities - Anam Pandoh; Ashish Singh (PLoS ONE, 2025)
Using the nationally representative Indian Human Development Surveys 2004–05 and 2011–12 and multiple inequality measures/frameworks, we investigate both vertical (within-group/interpersonal) and horizontal (between-group/inter group) socioeconomic (based on caste, religion, location and region) inequalities in wages among women in India. We find that the wage inequality (WI) is extremely high (around 60%) and has increased during 2004–12 driven by within-group inequalities which are very high and have increased, whereas between-group inequalities have reduced. There are stark rural-urban divides be it wage labour participation or mean wages; at the same time the WI itself is substantially higher in urban areas. Caste-based WIs are enormous with women belonging to scheduled groups and other backward castes earning substantially lower than their “upper” caste counterparts. The wages of Muslim women are consistently lower than women from other religions. There are vast inter-regional WIs, with the regions of Central and East having lower wages but higher inequalities.